Resistance of Clostridioides difficile spores (Clostridiales: Peptostreptococcaceae) to sodium dichloroisocyanurate - González-Carballo, Gian Carlo (2021)
Clostridioides difficile is a significant cause of diarrhea in hospitals and the community. This bacterial pathogen is transmitted through the ingestion of endospores, which are challenging to eliminate due to intrinsic resistance to a variety of chemical disinfection agents. The well-characterized laboratory strain CD630 displays low virulence, has not caused outbreaks, and is highly susceptible to disinfectants. Nonetheless, a closely related strain termed NAPCR1 caused outbreaks in Costa Rica and later became endemic in many hospitals from this country. This strain causes disease through unusual mechanisms and is genotypically distinct from CD630. Consequently, its epidemic potential could be influenced by as yet unknown spore phenotypes, such as increased resistance to disinfectants. Objective: To determine whether the NAPCR1 strain is more resistant to a conventional and highly effective C. difficile sporicidal agent than strain CD630 and to identify potential explanatory mechanisms at the genomic level. Methods: We used an in vitro dilution-neutralization method to calculate the sporicidal activity of sodium dichloroisocyanurate (DCC) against purified spores from three subtypes of NAPCR1 isolates (LIBA-2945, LIBA-5761, and LIBA-6276), CD630, and a representative of the highly virulent and epidemic NAP1 strain (LIBA-5758). This phenotypic characterization was complemented with a genomics-steered search of polymorphisms in 15 spore- or sporulation-related genes. Results: Whereas DCC at a final concentration of 0.1 % (w/v) eradicated CD630 endospores with high efficacy (log10 reduction factor (LFR) ≥ 5), it only partially inactivated NAPCR1 (average LFR range: = 1.77-3.37) and NAP1 endospores (average LRF = 3.58). As hypothesized, the three NAPCR1 subtypes tested were more resistant to DCC than strain CD630 (ANOVA, P < 0.05), with LIBA-5761 showing the highest level of DCC resistance overall (ANOVA, P < 0.05). All three NAPCR1 isolates showed large deletions in bclA1. Besides, isolates LIBA-5761 and LIBA-6276 had deletions in bclA2. Conclusions: Our in vitro tests revealed a differential resistance of spores from the C. difficile NAPCR1 strain to DCC. They highlight the importance of continuously evaluating the efficacy of deployed disinfection agents against circulating strains and hint to a potential role of structural proteins from the exosporium in resistance to disinfectants in C. difficile.